Editorial - Brunhari, Marcos; Barros, Rita; Darriba, Vinicius; Martins, Ana; Mollica, Mariana (Estudos e Pesquisas em Psicologia, 2023)
Marcos Vinicius Brunhari, Rita Maria Manso de Barros, Vinicius Darriba, Ana Carolina Borges Leão Martins, Mariana Mollica